2002
DOI: 10.1061/(asce)0899-1561(2002)14:4(355)
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Cracked Steel Fiber-Reinforced Concrete

Abstract: This research explores the relationship between permeability and crack width in cracked, steel fiber-reinforced concrete. In addition, it inspects the influence of steel fiber reinforcement on concrete permeability. The feedback-controlled splitting tension test (also known as the Brazilian test) is used to induce cracks of up to 500 microns (0.02in) in concrete specimens without reinforcement, and with steel fiber reinforcement volumes of both 0.5% and 1%. The cracks relax after induced cracking. The steel fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 2 publications
(3 reference statements)
1
43
0
5
Order By: Relevance
“…The study by Tsukamoto and Worner [24] indicated that the fibres in the concrete reduces the flow rate at a given crack width and increases the critical crack width below which no further flow occurs. Improved resistance against permeability of cracked steel fibre reinforced concrete and mortar over cracked ordinary concrete/mortar is also reported by Lawler et al [25] and Rapoport et al [26].…”
Section: Permeability Characteristics Of Cracked Shfrccsupporting
confidence: 58%
“…The study by Tsukamoto and Worner [24] indicated that the fibres in the concrete reduces the flow rate at a given crack width and increases the critical crack width below which no further flow occurs. Improved resistance against permeability of cracked steel fibre reinforced concrete and mortar over cracked ordinary concrete/mortar is also reported by Lawler et al [25] and Rapoport et al [26].…”
Section: Permeability Characteristics Of Cracked Shfrccsupporting
confidence: 58%
“…[36,37,38]. The results presented in this paper indicate that fibre reinforcement can also be beneficial in concrete elements with bending cracks, where multiple cracking is not visible at the surface but where branching occurs inside the concrete.…”
Section: Total Crack Width Vs Effective Crack Widthmentioning
confidence: 76%
“…If such agents reach reinforcing bars, the bars corrode, thus compromising the ability of the structure to withstand loads, which eventually leads to structural failure. Therefore, there has been an interest both in determining the permeability of lightweight concrete compared with normal weight concrete, and in the improvement of this type of concrete with lower permeability [1] .…”
Section: Introductionmentioning
confidence: 99%